(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation. Coronary artery disease (CHD) remains the leading cause of death in elderly patients. Recently, centers for revascularization therapy have been opened in almost all regions of our country. In particular, percutaneous coronary interventions (PCI) are used to effectively manage patients with ACS and PICS to improve the quality of life. These so-called endovascular interventions are currently a highly effective treatment method that can significantly improve the condition of patients and increase their tolerance to physical activity, return people to normal everyday life.